THE LINGUISTIC DILEMMA FOR AN EFFECTIVE ENGLISH LANGUAGE TEACHING METHODS - Obi, Nmadumelu; Shamir , Mohammed; D. Nwankwo, Kalu (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
There is no single most excellent way of teaching English as second language. Any successful language teacher will not confine himself to only a single method. A method which is appropriate with one class on one occasion will not necessarily suit to the same class at another time. Likewise, a method which is suitable for one language teacher while teaching a particular language item may not be applicable for other teacher in the same or similar context. Language learning is such a complex process that it is impossible to offer a single solution to all our language problems. Perhaps, the best method is the one which works, and this varies from context to context. It is against this backdrop, that this paper x-rays the tenets and strengths of the different English language teaching methods and finally, recommendations were given.